2016
DOI: 10.1371/journal.ppat.1006032
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Programmed Cell Death in Myeloid Cells on Host Resilience to Infection with Legionella pneumophila or Streptococcus pyogenes

Abstract: Pathogen clearance and host resilience/tolerance to infection are both important factors in surviving an infection. Cells of the myeloid lineage play important roles in both of these processes. Neutrophils, monocytes, macrophages, and dendritic cells all have important roles in initiation of the immune response and clearance of bacterial pathogens. If these cells are not properly regulated they can result in excessive inflammation and immunopathology leading to decreased host resilience. Programmed cell death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Rather, inducing apoptosis likely prevents excessive inflammation associated with Legionella infections, as the levels of the major inflammatory cytokines remained low in BCL-XL-deficient mice [23]. Consistent with this, overexpression of BCL-2 in macrophages and other innate immune cells leads to increased production of inflammatory cytokines in L. pneumophila-infected mouse lungs [24].…”
mentioning
confidence: 73%
“…Rather, inducing apoptosis likely prevents excessive inflammation associated with Legionella infections, as the levels of the major inflammatory cytokines remained low in BCL-XL-deficient mice [23]. Consistent with this, overexpression of BCL-2 in macrophages and other innate immune cells leads to increased production of inflammatory cytokines in L. pneumophila-infected mouse lungs [24].…”
mentioning
confidence: 73%
“…In a model of IAV infection, blockage of CCR2, the receptor expressed on monocyte-derived cells that facilitates their entry into the lung, results in decreased inflammatory cell infiltrate, inflammation, tissue damage, and mortality without any effect on viral clearance (105,106). It has also been shown that failure of these cells to induce programmed cell death during the resolution of infection results in unregulated, prolonged inflammation which in turn decreases tolerance (107)(108)(109)(110)(111).…”
Section: Decrease Of Innate Immunity-induced Damage Can Increase Hostmentioning
confidence: 99%
“…Mice overexpressing BCL-2 have also been used to determine the role of mitochondria-mediated cell death suggesting that apoptosis promotes pathogen clearance and/or dampens immune responses in infections. 21,50…”
Section: F I G U R E 1 Targeting Apoptosis Pathways By Bacteria Virumentioning
confidence: 99%
“…116 The fungal pathogen Histoplasma capsulatum secretes calcium-binding protein 1 (Cbp1) to trigger BAX-and BAK-mediated caspase activation, which is sufficiently lytic to promote escape from macrophages. 117,118 Overexpression of BCL-2 also reduces macrophage death in late-stage Legionella infections, 21,119 suggesting that Legionella activates apoptosis to escape from spent cells. Other cell death pathways likely contribute to Legionella-mediated killing of macrophages as well.…”
Section: Activation Of Apoptosis By Pathogensmentioning
confidence: 99%
See 1 more Smart Citation